2017
DOI: 10.1590/1678-457x.13417
|View full text |Cite
|
Sign up to set email alerts
|

Effect of temperature and nitrogen concentration on biomass composition of Heterochlorella luteoviridis

Abstract: The interest in microalga as a food supplement has grown due their high contents of carotenoids, polyunsaturated fatty acids and proteins. This study evaluated the effect of different temperatures (22, 27 or 32 °C) and sodium nitrate concentrations (12, 24, 36, 48 or 60 mg L -1 of N-ND 3 ) in culture medium on Heterochlorella luteoviridis biomass production and composition. The highest biomass concentration (3.35 g L -1) was observed at the highest N-ND 3 concentration. The N-ND 3 concentration positively aff… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
21
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 58 publications
(64 reference statements)
2
21
0
1
Order By: Relevance
“…The fatty acid profile of VCO oil was determined as fatty acid methyl esters (FAMEs), according to the previously reported method, 22 using gas chromatography (CG Model 2010; Shimadzu, Kyoto, Japan) and capillary column (30 m • 0.25 mm, and 0.25 mm). The chromatographic conditions were previously described by Menegol et al 23…”
Section: Determination Of Fatty Acid Methyl Estersmentioning
confidence: 99%
“…The fatty acid profile of VCO oil was determined as fatty acid methyl esters (FAMEs), according to the previously reported method, 22 using gas chromatography (CG Model 2010; Shimadzu, Kyoto, Japan) and capillary column (30 m • 0.25 mm, and 0.25 mm). The chromatographic conditions were previously described by Menegol et al 23…”
Section: Determination Of Fatty Acid Methyl Estersmentioning
confidence: 99%
“…Yang et al (2018) also observed that nitrogen-deficient conditions decreased the growth pattern for Chlamydomonas reinhardtii. Moreover, Menegol et al (2017) noticed a reduction in algal biomass of Heterochlorella luteoviridis under low nitrate concentration. However, the biomass productivity of studied strains was improved when cultured under nitrogen enrichment conditions.…”
Section: Discussionmentioning
confidence: 97%
“…In trial one, the average monthly temperature in the field was 18.9 to 22.8°C (Table 1) and in trial two, the temperature was 19.1-22.6°C; while in the greenhouse the temperature was 21-35.8 and 18.5-36.7°C in trial one and two respectively (Table 1). On the contrary, Menegol et al (2017) detailed that carotenes (βcarotene and lycopene) are not influenced by temperature.…”
Section: β-Carotenementioning
confidence: 97%